Funerary and related cups of the British Bronze Age - Copper, Claire, (Archaeopress Archaeology, 2022)
Cups are the least studied of all Bronze Age funerary ceramics and their interpretations are still based on antiquarian speculation. This book presents the first study of these often highly decorated items including a fully referenced and illustrated national corpus that will form the basis for future studies.